2016
DOI: 10.1002/ijc.30183
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease, cancer and medication: Cancer risk in the Dutch population‐based IBDSL cohort

Abstract: The management of inflammatory bowel disease (IBD) has changed since the mid-1990s (e.g., use of thiopurines/anti-TNFα agents, improved surveillance programs), possibly affecting cancer risk. To establish current cancer risk in IBD, updates are warranted from cohorts covering this time span, and detailed enough to study associations with phenotype and medication. We studied intestinal-, extra-intestinal- and overall cancer risk in the Dutch population-based IBDSL cohort. In total, 1,157 Crohn's disease (CD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 40 publications
2
49
1
Order By: Relevance
“…with tumour necrosis factor antagonists, often given for autoimmune conditions, may cause an increase in lymphoma incidence [55], although it cannot be entirely excluded either. In contrast, in Chron's disease, evidence is accumulating of a link between thiopurine medication and NHL risk [48].…”
Section: Autoimmune and Chronic Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…with tumour necrosis factor antagonists, often given for autoimmune conditions, may cause an increase in lymphoma incidence [55], although it cannot be entirely excluded either. In contrast, in Chron's disease, evidence is accumulating of a link between thiopurine medication and NHL risk [48].…”
Section: Autoimmune and Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Disorders most consistently associated with increased risks include Sjogren's syndrome, systemic lupus erythematosus, rheumatoid arthritis, autoimmune thyroiditis, coeliac disease and dermatitis herpetiformis [45,46]. Also, chronic inflammatory conditions such as Crohn's disease [47,48] and psoriasis [49] have often but not always been linked to increased lymphoma risks. An array of other immune-mediated disorders such as haemolytic anaemia, myositis and idiopathic trombocyopenic purpura have also been linked with lymphoma risk [45], although risks have been observed to peak around the time of diagnosis of the lymphoma, implying that these disorders may primarily occur as paramalignant autoimmune phenomena.…”
Section: Autoimmune and Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Notably, infliximab carries a “black box” warning regarding malignancies . Furthermore, a population‐based cohort study found that long‐term (>12 months) immunosuppression was associated with increased risk of haematologic cancer, non‐Hodgkin lymphoma, squamous cell skin cancer and overall cancer, primarily attributable to thiopurine use . In contrast, a registry‐based cohort study found no significant increase in cancer risk for patients with IBD receiving anti‐TNFα therapy vs no anti‐TNFα therapy over a median follow‐up of 3.7 years …”
Section: Introductionmentioning
confidence: 96%
“…Effect of thiopurines on the risk of nonmelanoma skin cancer. Eleven studies (two nested case-controls 26,27 and nine cohorts 7,8,18,[20][21][22][23][24]28 ) evaluated the association between thiopurines use and NMSC risk. Meta-analysis of nine cohort studies showed that thiopurines use increases the risk of NMSC (random effects: RR = 2.15, 95% CI 1.40-3.30, P < 0.001, Q = 21.43, P for heterogeneity 0.006, I 2 = 62.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of thiopurines on the risk of melanoma skin cancer. Four studies (two nested case-controls 26,27 and two cohorts 18,28 ) reported the risk of MSC in IBD patients after exposure to thiopurines. The association of thiopurines use with MSC was not statistically significant in either cohort studies (fixed effects: RR = 1.30, 95% CI 0.57-2.99, P = 0.531, Q = 1.18, P for Figure 2 Forest plots evaluating skin cancer risk in thiopurines-exposed versus thiopurines-unexposed groups.…”
Section: Meta-analysis Of Thiopurines Usementioning
confidence: 99%